The costs of organized violence : a review of the evidence - Stergios Skaperdas (Center for Economic Studies and ifo Institute (CESifo), 2009)
I critically review recent studies that estimate those costs of violence and conflict that can emerge among organized political groupings, from states, religious and ethnic organizations to guerillas and paramilitaries. The review includes studies that estimate direct and indirect costs due to internal conflicts (civil wars and other lower-level conflicts), terrorism, and external conflicts, including military spending. There are a number of key theoretical concerns on what counts as a cost, and, depending on the methods and evidence used, estimated costs vary widely. However, even minimum estimates are economically significant, especially for low-income countries. This is even more so when the costs of different types of organized conflict and violence are aggregated.
Keywords: D74; H56; I31; O57; 330; conflict; property rights; governance; Bürgerkrieg; Politische Gewalt; Politischer Konflikt; Soziale Kosten; Welt